UNVEILING HIDDEN MISCONCEPTIONS: A NEW PERSPECTIVE ON FIRST-YEAR STUDENTS' ALGEBRAIC UNDERSTANDING - Sari, Fadhila Kartika; Alifiani, Alifiani; Nursit, Isbadar; Jannah, Ukhti Raudhatul; Rahaju, Rahaju (Universitas Sembilanbelas November Kolaka, 2024)
This study aims to uncover and analyze hidden misconceptions in algebraic understanding among first-year students in the Mathematics Education Department at a private university in Malang. Conducted from January to March 2024, the research involves two first-year students as subjects. The first subject exhibits the misconception known as